If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5t + -18 = 12 + 3x Reorder the terms: -18 + 5t = 12 + 3x Solving -18 + 5t = 12 + 3x Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 5t = 12 + 18 + 3x Combine like terms: -18 + 18 = 0 0 + 5t = 12 + 18 + 3x 5t = 12 + 18 + 3x Combine like terms: 12 + 18 = 30 5t = 30 + 3x Divide each side by '5'. t = 6 + 0.6x Simplifying t = 6 + 0.6x
| 1+4i/4-i | | -7x-16=-5x | | 15p^2=20+20p | | 3y/8-9=y/8 | | 10q+3(5-2q)+4(7q+4)= | | 5x/-4=6x/8 | | 4/15z=1/10-4/9 | | 2x+1x+1x=180 | | -1+5=m-8 | | -4.90x^2-2.25x+1.92=0 | | y=1/2(8-1) | | 45-15-5(y+10)= | | x^2+0.0201x-0.0078591=0 | | 135-4x=41x+15 | | 7x-4(x-1)-3= | | 2/5-m/9=7/45 | | 1/5a+8=9 | | 0.70x+0.70(50)=0.35(98) | | y/3=y/5+8 | | 4+9(4-6m)=0 | | R-0.03=1.65 | | F+1.25=12.90 | | 63x^2-67x-18=0 | | 9.09+S=13.64 | | 3y+19=5y-7 | | 9.09+S= | | 5/6x=-2/18 | | -2y+2=-2(3y+11) | | 5.6+K=10 | | -3x=-6/9 | | 0.8-M=0.6 | | 1+1/x=90/x^2 |